2010
DOI: 10.1038/nature08991
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and AdipoR1 regulate PGC-1α and mitochondria by Ca2+ and AMPK/SIRT1

Abstract: Adiponectin is an anti-diabetic adipokine. Its receptors possess a seven-transmembrane topology with the amino terminus located intracellularly, which is the opposite of G-protein-coupled receptors. Here we provide evidence that adiponectin induces extracellular Ca(2+) influx by adiponectin receptor 1 (AdipoR1), which was necessary for subsequent activation of Ca(2+)/calmodulin-dependent protein kinase kinase beta (CaMKKbeta), AMPK and SIRT1, increased expression and decreased acetylation of peroxisome prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
771
7
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 901 publications
(854 citation statements)
references
References 45 publications
35
771
7
10
Order By: Relevance
“…The current study revealed that AD supplementation could reverse hypoadiponectinemia and mitochondrial dysfunction associated with CIH [3]. Anthony E. and other studies have shown that AD could increase PGC1-a expression to promote mitochondrial content in skeletal muscle cells [9,11]. Consistent with our results, AD supplementation could promote GG mitochondrial synthesis even under CIH conditions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The current study revealed that AD supplementation could reverse hypoadiponectinemia and mitochondrial dysfunction associated with CIH [3]. Anthony E. and other studies have shown that AD could increase PGC1-a expression to promote mitochondrial content in skeletal muscle cells [9,11]. Consistent with our results, AD supplementation could promote GG mitochondrial synthesis even under CIH conditions.…”
Section: Discussionsupporting
confidence: 81%
“…Chronic activation of AMP kinase can result in enhanced mitochondrial biogenesis and oxidative capacity [33]. AD can stimulate glucose utilization and fatty acid oxidation by activating AMP-activated protein kinase [11,34]. Our study demonstrated that CIH partially inhibited the expression of AMPK pathway, whereas AD supplementation could imminently elevate the expression of LKB1 (AMPKK)/AMPK/PGC1-a.…”
Section: Discussionmentioning
confidence: 67%
“…We choose MMP-1, ADIPOR1, and DTX3L for follow-up due to their high expression in Ewing tumors and their involvement in oxidative stress responses (34,38,39). Notably, (Fig.…”
Section: Ros Are Critical For Ewing Tumor Proliferation and Invasivenessmentioning
confidence: 99%
“…On the other hand, the activity of PGC-1α is probably directly modulated through pathways that depend on sirtuin 1 (SIRT1), an NAD + -dependent deacetylase [27][28][29] . PGC-1α could interact with and activate various kinds of transcription factors, and regulate expression of various metabolism-related genes 25) .…”
Section: Molecular Regulators Of Metabolic Adaptation In Peripheral Tmentioning
confidence: 99%